Expressão de coerção em assistência de pacientes atendidos num hospital universitário - Bittencourt, Ana Luiza Portela (2010)
This work approaches the perception of coercion, on the part of the patient, n the process of informed consent which constitutes an important element in health. The perception of coercion may be associated with this practice so that the subject perceives that has not been able to express their will with respect to its treatment. One searched to evaluate if the patient perceived himself able to express his opinion in the authorization process for the realization of care procedures and understand the involved factors in this perception, according to these subjects. Also one used instruments of evaluation of the level of literacy and development psychological-moral in order to better understand the factors involved in decision making in healthcare. The present work consists in a transversal study, which was applied Expression Scale of Coercion in Care, the Instrument of Evaluation of the Development Psychological-moral and the instrument of Evaluation of Literacy in two samples: one consisting of 143 outpatients and another of 142 patients admitted to HUSM. The technique of half-structuralized interview was also used to understand the factors that had taken the patients to indicate discomfort in expressing themselves. These subjects constitute a sub-sample, consisting of six subjects who responded to the questionnaires mentioned above showing some degree of expression of coercion on the scale applied in order to evaluate this data. In the found results, the relative data to this measure are not differentiated between the samples, and indicate a low level of perception of coercion when expressing itself. It was observed that the research subjects, in its majority, meet in the concientious level of the development scale psychological-moral. In both the samples had prevalence of the rudimentary level of literacy. In sub-sample interviewed may be noted the identification by the patient, of whom did not have voice in the treatment seems linked to the supply of information, the experiences with the hospital, and also the elements as the time of attachment to the institution, the gratitude and the way as the experiences had been integrated psychically by the subject